Proposição de uma sistemática para avaliação qualitativa da oferta hídrica superficial aplicada em sub-bacias hidrográficas da Bacia Hidrográfica do Rio Piracicaba - Região Sudeste do Estado de São Paulo - Carvalho, Ana Claudia Pereira (Universidade Federal de São Carlos, 2022)
Currently, one of the global concerns is to meet the present water demand, without compromising the quantity and water quality for the next generations. Globally, it is known that climate change is intensifying the phases of the hydrological cycle, which when altered cause extreme events, being common to report regions in severe drought and locations that suffer from impacts from high intensities of precipitation. In addition, more attention should be paid to pressures on water resources, such as growing demand, a reflection of world population growth, agricultural productivity, expansion of the industrial sector, and changes in land use and cover. In this sense, this work was developed in the 4th order of the hydrographic sub-basins of the Piracicaba River Basin (BHRP), located in the southeast region of the State of São Paulo, which presents contemporaneously a water criticality per capita. The study consists of qualitatively classifying the 180 sub-basins as to the surface water supply considering the rainy semester, the dry semester and the average accumulated in the period from 2011 to 2020. Of these sub-basins, four pairs of sample areas were chosen defined by means of a cluster analysis based on morphometric indices and area, which were called Study Objects Hydrographic Sub-basins (SBH-OE). In the SBH-OE, rainfall and fluviometric monitoring were performed (from May 2019 to April 2020), in addition to mapping the physical and anthropic means, in order to understand the water dynamics of each pair, for this were carried out: flow rate analysis measured in situ with reference flows; rainfall x flow rate correlations; analysis of the attributes of the physical environment, through the elaboration of Charts of Potential to Surface Runoff (CPES) for SBH-OE. These analyses carried out in the SBH-OE allowed to understand the water behavior, thus making it possible to assist in the classification of the hydrographic sub-basins in terms of surface water supply. For this classification required the realization of intermediate interpretive charts (Charter of Importance of Territorial Coverage of Water Catchment Sub-Basins-CIAT, CPES and the Charter of Difference between Rainfall and Royal Evapotranspiration-CDPE). Sequentially, by means of the AHP (Analytic Hierarchy Process) technique, these information plans and their respective classes were weighted, superimposed and summed in the Arcgis10.5.1® software. Finally, each hydrographic sub-basin was classified according to the predominant class, considering the rainy semesters (COHS-SC) and dry (COHS-SS) and the accumulated average (COHS-MA). Thus, COHS-SC classified 11 sub-basins as Very Low, 159 (Low), 10 (Middle). COHS-SS presents 174 sub-basins classified as Very low, 6 (Low). Regarding COHS-MA, 5 were classified as Very low, 112 (Low), 60 (Middle), 3 (High). It is worth mentioning that the methods approached can be applied in any hydrographic region that has the data used in this study. The results of this work may assist managers and planners in decision-making and in the elaboration of public policies aimed at minimizing the negative impacts on water resources.
Proposal for a system for qualitative assessment of the surface water supply applied in the hydrographic sub-basins of the Piracicaba River Basin - Southeast region of the state of São Paulo
Keywords: Bacias hidrográficas; Escoamento superficial; Oferta hídrica superficial; Pluviosidade; Sistema de Informações Geográficas; Vazão; AHP; Watersheds; Runoff; Surface water supply; Rainfall; Geographical Information System; Flow rate; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA::HIDROLOGIA; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOFISICA::SENSORIAMENTO REMOTO; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::GEOCARTOGRAFIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::PEDOLOGIA; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA REGIONAL::ANALISE REGIONAL; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA REGIONAL::REGIONALIZACAO; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::CARTOGRAFIA GEOLOGICA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::GEOLOGIA AMBIENTAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS